기업의 디지털트랜스포메이션 역량이 서비스 혁신 행동에 미치는 영향 연구 - 왕위빈(Wei-Bin Wang); 박상오(Sang-Oh Park); 김상현(Sang-Hyun Kim) (디지털콘텐츠학회논문지, 2021)
본 연구는 기업의 디지털트랜스포메이션 역량의 활용과 탐색이 디지털트랜스포메이션 역량이 서비스 혁신행동에 영향을 미치는 과정에서 어떠한 매개역할을 하는지를 알아보고자 함에 있다. 선행연구를 토대로 요인별 측정항목 도출과 연구모형, 그리고 설문 조사를 통한 분석방법을 진행하였다. 분석결과는 디지털트랜스포메이션 역량은 서비스혁신행동과 디지털트랜스포메이션 활용과 탐색에, 그리고 디지털트랜스포메이션 활용과 탐색이 서비스 혁신행동에 영향을 미치고 있음을 보여주었다. 또한 디지털트랜스포메이션 활용과 탐색은 디지털트랜스포메이션 역량이 서비스혁신행동에 영향을 미침에 있어 부분 매개역할을 하였다. 이러한 결과는 기업의 디지털트랜스포메이션 역량, 활용과 탐색, 그리고 서비스혁신행동을 위한 지속적인 노력의 필요성에 대한1 함의와 고객과의 관계가 유지되도록 해야 함을 시사한다. 본 연구결과는 기업의 디지털트랜스포메이션 역량 강화와 활용을 위한 참고자료가 될 것이다. This study aims to find out how the utilization and exploration of a company's digital transformation capabilities play a role as a medium in the process in which digital transformation capabilities affect service innovation behaviors. Based on prior research, the analysis method was carried out through the derivation of measurement items by factor, research model, and survey. Analysis results showed that digital transformation capabilities affect service innovation behaviors, utilization and exploration of digital transformation, and utilization and exploration of digital transformation. Furthermore, digital transformation utilization and exploration played a partial role in the impact of digital transformation capabilities on service innovation behavior. These results suggest that 1 implications of an entity's digital transformation capabilities, utilization and exploration, and the need for continuous efforts to act on service innovation should be maintained and that relationships with the customer should be maintained. The results of this study will be a reference material for companies to strengthen and utilize their digital transformation capabilities. KCI Citation Count: 5